Monitoring of an ascending air bubble in a viscous fluid/fiber matrix medium using a phased array transducer - Samet, Naïm; Marechal, Pierre; Duflo, Hugues (European journal of mechanics, B, Fluids, 2015)
Detecting porosities of different scales, both micro and macro, is a current problem in the development of composite materials. This is especially true for composite materials manufactured using Resin Transfer Molding (RTM). When injecting resin in the fibrous preform porosities appear, originating essentially because of air trapped in the fiber matrix. Consequently, the interaction between air bubbles and fibers has been the subject of several numerical investigations. In this study, we propose an original experimental method to monitor the interaction of air bubbles with a fibrous matrix. A 10 MHz center frequency ultrasonic phased array transducer is used to monitor air bubbles in the millimeter range. The ultrasonic imaging method is first tested only with bubbles ascending in a channel containing silicone oil. Then it is tested again in a sample of fiber matrix immersed in the same channel. The results prove the effectiveness of the measurement process. These results then can be used to find a correlation between the appearance of porosities and the processes that generate them in order to consider how to improve RTM. They can also be used to understand the interaction phenomena between bubbles and folds in order to improve RTM process.